Courting Dissolution Adumbration, Alterity, and the Dislocation of Sacrifice from Space to Image - Lent, Michael (Image, 2016)
Michael Lent asks what role art has in colonisation and subsequent dissolution. He proposes a practice informed by the fatal strategies and 'raw' phenomenology of Jean Baudrillard as a challenge to a system of disappearance. Focusing on the otherness of space to prevent its ultimate dissolution, Lent promotes a spatial practice of radical alterity. Examining ideas of disappearance put forth by Baudrillard and Paul Virilio, he utilises art as a means for investigating loss of potentiality and experience through the representation of space, shifting their ideas - originally ascribed to objects - into a new emphasis.This book ultimately attempts to break a cyclical system that causes everything to disappear into representation and equivalency